You are on page 1of 6

# Partial–Fraction Decomposition

1. Introduction
In earlier chapters, you are working with two or more rational algebraic
expressions – combining them into a single expression either by addition or
subtraction. For example,

2
3 2 5

2 1
x
x x x
÷
+
÷ + ÷
=
2
3 2
5 6 7
3 2
x x
x x x
÷ +
÷ ÷ +

The terms on the left side of the equation are called the partial–fraction
decomposition of the rational algebraic expression on the right side.

This chapter mainly talks about the reverse problem, that is, to write a
complicated rational algebraic expression as a sum or difference of several
simpler rational algebraic expressions.

2. The Condition for Partial–Fraction Decomposition
In order to decompose a rational algebraic expression into simpler
expression, it must satisfy the following condition:

degree of the numerator < degree of the denominator

Consider the following rational algebraic expressions:

2
3
3 4
,
1
x
x
÷
+

3 2
4 2
10 6 2
,
5 4
x x x
x x
+ ÷ +
÷ +

( )( )
5 3
2
2
2 3
x x
x x x
÷ +
÷ +

Observe that the first two fractions have numerators with degrees lesser
than that of the denominators while the third fraction has a numerator with greater
degree than that of the denominator. Thus, the method of partial–fraction
decomposition can be directly applied to both the first and the second fraction. On
the other hand, use the long division algorithm with the third fraction in order to
reduce it into a form that satisfies the basic condition.

3. The Decomposition Process
Once the condition for the degree is satisfied, partial–fraction
decomposition may now be use. To start, factor the denominator into a product
where each of the factors is either of the forms
( )
m
dx e + or
( )
2
n
ax bx c + +
with , m n
+
e and , , , , . a b c d ee Also, the factor
2
ax bx c + + should be an
2
ax bx c + + should have no real roots.
Then, use the following rules:
a. For each factor ( ) ,
m
dx e + the partial–fraction decomposition
includes the terms

( ) ( )
1 2
2
.
m
m
A A A
dx e
dx e dx e
+ + +
+
+ +

( )

b. For each factor
( )
2
,
n
ax bx c + + the partial–fraction decomposition
includes the terms

( ) ( )
1 1 2 2
2 2
2 2
.
m m
m
B x C B x C B x C
ax bx c
ax bx c ax bx c
+ + +
+ + +
+ +
+ + + +

( )
††

Remember that these rules are only limited up to powers of quadratic
factors. Any extension will be dealt in a separate paper or book.

Finally, use algebraic methods to determine the values of the ' , A s the
' , B s and the ' . C s

4. The Factors of the Denominator
The denominator should be factored in order to start the partial–fraction
decomposition process. Once it is not factorable, then the decomposition cannot
be use. Let us discuss the possibilities of the factors.

Distinct Linear Factors
Consider the fraction
2
3 2
6 28 18
.
6
x x
x x x
÷ ÷
+ ÷
The denominator
3 2
6 x x x + ÷ can
be factored as ( )( ) 2 3 . x x x ÷ + Thus, by partial–fraction decomposition,

2
3 2
6 28 18
6
x x
x x x
÷ ÷
+ ÷
= .
2 3
A B C
x x x
+ +
÷ +
( ) i

Multiply both sides by the denominator and you will obtain the equation

2
6 28 18 x x ÷ ÷ = ( )( ) ( )( ) ( )( ) 2 3 3 2 . A x x B x x C x x ÷ + + + + ÷ ( ) ii
=
( ) ( ) ( )
2 2 2
6 3 2 . A x x B x x C x x + ÷ + + + ÷

Then, combine similar terms and get

2
6 28 18 x x ÷ ÷ = ( ) ( )
2
3 2 6 . A B C x A B C x A + + + + ÷ ÷

By comparing the terms, you will get the following equations:
A B C + + = 6, 2 2 A B C + ÷ = 28, ÷ 6A ÷ = 18 ÷
and from which, the values 3, A= 5, B = ÷ and 8 C = can be obtained. Therefore,

2
3 2
6 28 18
6
x x
x x x
÷ ÷
+ ÷
=
3 5 8
.
2 3 x x x
÷ +
÷ +

where the right side of ( ) i forms the decomposition of the given fraction.

Alternatively, a similar yet effective strategy can be utilized. Consider ( ) ii
of the last example, written as

2
6 28 18 x x ÷ ÷ = ( )( ) ( )( ) ( )( ) 2 3 3 2 . A x x B x x C x x ÷ + + + + ÷

This polynomial is an identity, and you may substitute any three values of
x to determine the three constants , , and . A B C It can be shown (by continuous
functions) that zeros of ( ) ii may be used even though the original fraction is not
defined on these points. Thus, using 0, 2, and –3,
0: at x = 18 ÷ = ( )( ) 2 3 A ÷ ÷ and hence A =
18
3.
6
÷
=
÷

2: at x = 24 56 18 ÷ ÷ = ( )( ) 2 5 B and hence B =
50
5.
10
÷
= ÷
3: at x = ÷ 54 84 18 + ÷ = ( )( ) 3 5 C ÷ ÷ and hence C =
120
8.
15
=
which yield the same results.

Powers of Linear Factors
In the first example, all linear factors are of the first degree. Thus, you
only have to follow ( ) † . In the next example, a denominator with linear factors
but not of the first degree will be treated.

Consider the fraction
( ) ( )
2
1
.
1 2 x x + +
Since the factor ( ) 1 x + occurs with
degree 2 and ( ) 2 x + with degree 1, then by ( ) † ,

( ) ( )
2
1
1 2 x x + +
=
( )
2
.
1 2
1
A B C
x x
x
+ +
+ +
+
( ) iii

Following the same procedure as the first example, you will get
1 = ( )( ) ( ) ( )
2
1 2 2 1 . A x x B x C x + + + + + +

Choose any three values of , x in this case, 1, 2, 0. x = ÷ ÷ Then,
1: at x = ÷ 1 = ( ) 1 2 A ÷ + and hence A = 1.
2: at x = ÷ 1 = ( )
2
2 1 C ÷ + and hence C = 1.
0: at x = 1 = ( )( ) ( ) ( )
2
0 1 0 2 0 2 0 1 A B C + + + + + +
1 = ( ) ( ) 2 1 2 1 B + + and hence B = 1. ÷

Therefore, ( ) iii becomes

( ) ( )
2
1
1 2 x x + +
=
( )
2
1 1 1
.
1 2
1
x x
x
÷ +
+ +
+

There is always a possibility that the denominator has quadratic factors,
especially when it is of degree 3 or higher. It should be noted that these quadratic
factors must be irreducible so that ( ) †† can be used. Remember that
2
ax bx c + +
is irreducible if
2
4 0 b ac ÷ < or if
2
4 . b ac a perfect square ÷ =

Consider the fraction
( )
( )
2
2
5 6 10
.
2 3 4
x x
x x x
÷ +
+ ÷ +
Here, the denominator was
already factored and ( ) ( )( )
2
2
4 3 4 1 4 7 b ac ÷ = ÷ ÷ = ÷ and the factor
2
3 4 x x ÷ + is
irreducible. Thus, by ( ) † ,

( )
( )
2
2
5 6 10
2 3 4
x x
x x x
÷ +
+ ÷ +
=
2
2 3 4
A Bx C
x x x
+
+
+ ÷ +

Multiplying both sides by the denominator, you will obtain

2
5 6 10 x x ÷ + =
( )
( )( )
2
3 4 2 A x x Bx C x ÷ + + + + ( ) iv
When 2, x = ÷
( ) ( )
2
5 2 6 2 10 ÷ ÷ ÷ + = ( ) ( )
2
2 3 2 4 A
(
÷ ÷ ÷ +
¸ ¸

20 12 10 + + = ( ) 4 6 4 A + + hence A = 3.

After collecting similar terms in ( ) , iv you will have

2
5 6 10 x x ÷ + = ( ) ( )
2
3 2 4 2 . A B x A B C x A C + + ÷ + + + +

Since no other real x that will make a factor zero, comparing the terms of
both sides will be an option. Thus,
A B + = 5, 3 2 A B C ÷ + + = 6, ÷ 4 2 A C + = 10.

Substituting 3, A= we obtain 2 B = and 1. C = ÷ This avoids us in having
to solve for the systems of equations.
Similarly, polynomials may have powers of quadratic as factors. The
condition is similar to the previous case except that it may have powers of two or
more.
Consider the fraction
( )
( )
4 3 2
2
2
5 7 27 19 21
1 2
x x x x
x x
÷ + ÷ +
÷ +
and decompose it into
sum or difference of simpler fractions. Then, by ( ) †† ,

( )
( )
4 3 2
2
2
5 7 27 19 21
1 2
x x x x
x x
÷ + ÷ +
÷ +
=
( )
2 2
2
1 2
2
A Bx C Dx E
x x
x
+ +
+ +
÷ +
+

4 3 2
5 7 27 19 21 x x x x ÷ + ÷ + =
( )
( )
( )
( ) ( )( )
2
2 2
2 2 1 1 . A x Bx C x x Dx E x + + + + ÷ + + ÷
When 1, x = 5 7 27 19 21 ÷ + ÷ + =
( )
2
2
1 2 A + and 3. A= With similar
processes, you have

( )
( )
( )
( ) ( )( )
2
2 2
2 2 1 1 A x Bx C x x Dx E x + + + + ÷ + + ÷
4 2 4 3 2 3 2
4 4 2 2 2 2 Ax Ax A Bx Bx Bx Bx Cx Cx Cx C = + + + ÷ + ÷ + ÷ + ÷
2
Dx Dx Ex E + ÷ + ÷
( ) ( ) ( ) ( )
4 3 2
4 2 2 2 A B x B C x A B C D x B C D E x = + + ÷ + + + ÷ + + ÷ + ÷ +
4 2 . A C E + ÷ ÷

and obtain the following equations:
A B + = 5 2 2 B C D E ÷ + ÷ + = 19 ÷
B C ÷ + = 7 ÷ 4 2 A C E ÷ ÷ = 21
4 2 A B C D + ÷ + = 27

Since 3, A= then by substitution, 2, B = 5, C = ÷ 6, D = and 1. E =
Using this technique, solving system of equations involving three or more
unknowns may be avoided.

Powers of Linear and Quadratic Factors
Consider the fraction
( )
( )
6 5 4 3 2
2
2
2
2 19 83 206 297 234 50
1 3 5
x x x x x x
x x x x
÷ + ÷ + ÷ +
÷ ÷ +

whose denominator is already in factored form. Then, by ( ) † and ( ) †† , the
fraction can be written as

( )
( )
6 5 4 3 2
2
2
2
2 19 83 206 297 234 50
1 3 5
x x x x x x
x x x x
÷ + ÷ + ÷ +
÷ ÷ +

( )
( )
2 2 2
2
1 3 5
1
3 5
A B C Dx E Fx G
x x x x
x
x x
+ +
= + + + +
÷ ÷ +
÷
÷ +

Multiplying both sides by ( )
( )
2
2
2
1 3 5 , x x x x ÷ ÷ + you have
6 5 4 3 2
2 19 83 206 297 234 50 x x x x x x ÷ + ÷ + ÷ +
( )
( )
( )
( ) ( )
2 2 2
2
2 2 2
1 3 5 1 3 5 3 5 A x x x Bx x x x Cx x x = ÷ ÷ + + ÷ ÷ + + ÷ +
( ) ( )
( )
( ) ( )
2 2
2
1 3 5 1 Dx E x x x x Fx G x x + + ÷ ÷ + + + ÷
When 0: x = ( ) ( )
2 2
50 1 5 2. A A = ÷ ÷ =
When 1: x = ( )
( )
2
2
2 19 83 206 297 234 50 1 1 3 5 3. C C ÷ + ÷ + ÷ + = ÷ + ÷ = ÷

Expanding and collecting similar terms, the right side becomes
( ) ( ) ( )
6 5 4
8 7 32 25 6 A B x A B C x A B C D F x = + + ÷ ÷ + + + ÷ + +
( )
3
74 49 19 2 2 25 A B C D E F G x A + ÷ ÷ + ÷ + ÷ + +
( ) ( )
2
104 55 30 2 2 80 25 25 A B C D E F G x A B C E G x + + ÷ + ÷ + ÷ + ÷ ÷ + + +

Comparing terms of both sides, you have
2 0; A B B + = ÷ = 32 25 6 83 1; A B C D F D F + ÷ + + = ÷ + =
74 49 19 2 2 206 1; A B C D E F G E G ÷ ÷ + ÷ + ÷ + = ÷ ÷ + =

Since we have two equations only, we create two more equations.
When 1: x = ÷
324 162 81 36 36 4 4 891 9 9 0. A B C D E F G D E F G + ÷ + ÷ + ÷ = ÷ ÷ + ÷ =
When 2: x =
9 18 18 12 6 4 2 30 6 3 2 3. A B C D E F G D E F G + + + + + + = ÷ ÷ + + + =

By method of substitution or elimination, you get 0, D = 0, E = 1, F =
and 1. G =

Hence,

( )
( )
6 5 4 3 2
2
2
2
2 19 83 206 297 234 50
1 3 5
x x x x x x
x x x x
÷ + ÷ + ÷ +
÷ ÷ +

( )
( )
2 2
2
1 3 1
1
3 5
x
x
x
x x
+
= ÷ +
÷
÷ +

and this completes the required decomposition.